Prevalence, Predictive Factors, and Outcomes of Respiratory Failure in Children With Pneumonia Admitted in a Developing Country - Shaima, Shamsun Nahar; Alam, Tahmina; Bin Shahid, Abu Sadat Mohammad Sayeem; Shahrin, Lubaba; Sarmin, Monira; Afroze, Farzana; Parvin, Irin; Nuzhat, Sharika; Jahan, Yasmin; Mamun, Gazi Md. Salahuddin; Saha, Haimanti; Ackhter, Mst. Mahmuda; et al. (Frontiers in Pediatrics, 2022)
Background Pneumonia has been the leading infectious cause of morbidity and mortality in children under 5 years of age for the last several decades. Although most of these deaths occur due to respiratory failure, published data are limited regarding predicting factors and outcomes of respiratory failure in children hospitalized with pneumonia or severe pneumonia. Objective This study aimed to explore the prevalence, predicting factors, and outcomes of respiratory failure in children under-five with pneumonia or severe pneumonia. Methods In this retrospective chart analysis, we enrolled children under 5 years of age hospitalized with pneumonia or severe pneumonia in the Dhaka Hospital of International Centre for Diarrheal Disease Research, Bangladesh (icddr,b) between August 2013 and December 2017. Comparisons were made between children with respiratory failure (n = 212) and those without respiratory failure (n = 4,412). Respiratory failure was defined when the oxygen saturation/fraction of inspired oxygen (SpO2/FiO2) was <315. Results A total of 4,625 children with pneumonia or severe pneumonia were admitted during this study period. Among them, 212 (4.6%) children developed respiratory failure and formed the case group. A total of 4,412 (95.3%) children did not develop respiratory failure and formed the comparison group. In logistic regression analysis, after adjusting with potential confounders, severe sepsis [adjusted odds ratio (aOR): 12.68, 95% CI: 8.74–18.40], convulsion (aOR: 4.52, 95% CI: 3.06–6.68), anemia (aOR: 1.76, 95% CI: 1.20–2.57), and severe underweight (aOR: 1.97, 95% CI: 1.34–2.89) were found to be independently associated with respiratory failure. As expected, children with respiratory failure more often had fatal outcome than without respiratory failure (74, 1%, p < 0.001). Conclusion The results of our analyses revealed that prevalence of respiratory failure was 4.6% among under-five children hospitalized for pneumonia or severe pneumonia. Severe sepsis, convulsion, anemia, and severe underweight were the independent predictors for respiratory failure in such children and their case-fatality rate was significantly higher than those without respiratory failure. Early recognition of these predicting factors of respiratory failure may help clinicians imitating prompt treatment that may further help to reduce deaths in such children, especially in resource-limited settings.